2017
DOI: 10.1093/milmed/usx025
|View full text |Cite
|
Sign up to set email alerts
|

A Tertiary Care Center’s Experience with Novel Molecular Meningitis/Encephalitis Diagnostics and Implementation with Antimicrobial Stewardship

Abstract: The ME panel appears to improve diagnostic yield in our facility, and there is potential for improvement in decreasing empiric antimicrobial usage, particularly in patients with a negative ME panel and absence of CSF pleocytosis. This demonstrates the need for antibiotic stewardship program involvement to assist in implementation of rapid diagnostic tests through methods such as education, clinical guidelines, and prospective audit and feedback to improve meningitis and encephalitis management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…This is one of the first studies to evaluate the clinical impact of an in-house multiplex PCR assay on the care of adult patients admitted from the community with a suspected CNS infection. Similar to prior studies, we found a significantly reduced diagnostic TAT and a reduction in antiviral therapy [2,7,9,10,14]. Additionally, our study included a diverse patient population by incorporating both a quaternary academic referral center as well as a community-based teaching hospital.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is one of the first studies to evaluate the clinical impact of an in-house multiplex PCR assay on the care of adult patients admitted from the community with a suspected CNS infection. Similar to prior studies, we found a significantly reduced diagnostic TAT and a reduction in antiviral therapy [2,7,9,10,14]. Additionally, our study included a diverse patient population by incorporating both a quaternary academic referral center as well as a community-based teaching hospital.…”
Section: Discussionsupporting
confidence: 78%
“…Often, patients that undergo CSF analyses remain on broad antimicrobial coverage while waiting days for diagnostic results [2]. This delay can result in preventable harm from unnecessary drug exposure, as well as prolonged hospital stays.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular tools allowing a syndromic approach to M/E diagnosis have become available. As the results are available in around 1 hour, these approaches are of great interest despite their costs, considering the clinical importance of M/E and the potential for improvement in adequate antimicrobial treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study evaluated the cost-effectiveness of setting up the ME panel, it was found that the main benefit from the economic point of view was in the decrease in the consumption of antimicrobials [16]. This finding contrasts with another study [10] where there was no timely suspension of inappropriate therapy according to the results of the panel, which reinforces the importance of the implementation of the test in the context of an antimicrobial stewardship programme.…”
Section: Discussionmentioning
confidence: 98%
“…The main limitation of this panel is with C. neoformans where it can be as low as 50% [8]. So far, studies have been carried out mainly in the pediatric population and in immunocompetent patients with overall good performance, although only approximately 25% of the film array panels are positive [9, 10]. Currently, there are no studies evaluating the performance of this panel in Latin America.…”
Section: Introductionmentioning
confidence: 99%